Pengembangan Video Pembelajaran Berbasis Edpuzzle sebagai Bahan Ajar Pelajaran Al-Qur’an Hadis Materi Surah Al-A’la Kelas VIII MTsN 1 Palangkaraya - Khairunnisa, Khairunnisa; Jasiah, Jasiah (Lembaga Yasin AlSys, 2025)
The low level of student participation and understanding in Al-Qur’an Hadis instruction—particularly in the study of Surah Al-A’la—poses a challenge to creating an effective and meaningful learning process. This study aims to develop an interactive video-based learning medium using Edpuzzle, tailored to the characteristics of eighth-grade students and designed to enhance their comprehension of the material. The research employed the ASSURE development model, which includes analyzing learners' needs and characteristics, defining learning objectives, selecting relevant media, integrating digital technology, engaging learners actively, and conducting media evaluation and revision. Validation results indicate that the Edpuzzle interactive video received feasibility scores of 83% from media experts and 81% from content experts, suggesting it is suitable for instructional use. A trial involving 20 students yielded a positive response, with an average satisfaction rate of 90%. Students reported that Edpuzzle made learning more enjoyable, varied, and helpful in understanding the content of Surah Al-A’la through visualization and interactive features. These findings conclude that Edpuzzle positively contributes to improving student motivation and comprehension by delivering content in a structured and communicative manner. The implications suggest that interactive digital media such as Edpuzzle are appropriate for broader application in religious education and hold potential to foster students’ critical thinking skills and digital literacy in the technological era.